Harnessing the potential of artificial intelligence to promote environmental sustainability - Majumdar, Parijata; Nag, Aniruddha; Navarro, Diego Alberto Oliva (Emerald Publishing Limited, 2026)
Harnessing the Potential of Artificial Intelligence to Promote Environmental Sustainability provides a comprehensive examination of how AI is transforming environmental conservation and sustainability efforts. This scholarly work delves into cutting-edge AI technologies--such as automation, data analytics, and machine learning--and explores their potential to address pressing environmental challenges. Through in-depth analysis and practical case studies, the book demonstrates how AI can enhance resource management, support sustainable practices, and improve environmental monitoring. Beyond technical solutions, the authors engage with the ethical considerations and potential risks of deploying AI in environmental contexts. Issues such as fairness, transparency, and accountability in AI systems are explored, along with the need for regulatory frameworks to mitigate negative impacts. An essential resource for researchers, professionals, policymakers, and anyone interested in the intersection of technology and environmental stewardship, this contributed work offers a roadmap for leveraging AI to foster a sustainable future, emphasising the crucial role of advanced technologies in addressing global environmental challenges.
Includes index.
Keywords: Artificial intelligence -- Environmental aspect.; Sustainable development.; Computers -- Artificial Intelligence -- General.; Artificial intelligence.; elektronické knihy; electronic books